STUDI TENTANG PRODUK ANYAMAN BAMBU DI NAGARI KOTO BARU SIMALANGGANG KECEMATAN PAYAKUMBUH - MUHAMMAD LERI CANIAGO, Dra. Jupriani, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (Serupa The Journal of Art Education, 2019)
The purpose of this experiment is (1) To know the hecniquethat used to make bamboo woven. (2) To knowthe shape of bamboo.(3) To know the function of bamboo woven. (4) Name of motive from Nagari Koto Baru Simalanggang. (5) there is two type data sources of this experiment, that is premier data dan secunder data. Method that used is observation, interview and documentation. Finding result from this experiment, the shape of motive the find in Nagari Koto Baru Simlanggang is geometric. That is triangle shape and rectangular shape.Kata kunci: anyaman, produk, skripsi